(untitled) (Pesquisa Odontológica Brasileira, 2002)
The purpose of this study was to morphologically evaluate, by means of scanning electron microscopy, the effects of Er:YAG laser on the treatment of root surfaces submitted to scaling and root planing with conventional periodontal instruments. Eighteen root surfaces (n = 18), which had been previously scaled and planed, were assigned to 3 groups (n = 6). The control Group (G1) received no further treatment; Group 2 (G2) was irradiated with Er:YAG laser (2.94 mum), with 47 mJ/10 Hz, in a focused mode with air/water spray during 15 s and with 0.57 J/cm² of fluency per pulse; Group 3 (G 3) was irradiated with Er:YAG laser (2.94 mum), with 83 mJ/10 Hz, in a focused mode with air/water spray during 15 s and with 1.03 J/cm² of fluency per pulse. We concluded that the parameters adopted for Group 3 removed the smear layer from the root surface, exposing the dentinal tubules. Although no fissures, cracks or carbonized areas were observed, an irregular surface was produced by Er:YAG laser irradiation. Thus, the biocompatibility of the irradiated root surface, within the periodontal healing process, must be assessed.